PEMANFAATAN CHROMEBOOK DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR NEGERI 18 SUNGAI KAKAP - Hery Kresnadi; Siti Halidjah; Rio Pranata; Husni Syahrudin (STKIP Persada Khatulistiwa Sintang, 2023)
The success of Indonesia's education digitization program is highly dependent on the readiness of three aspects that can at least be said to be good enough in responding to digital-based education namely, regulators, teachers or teachers, and students. With the government assistance program in the form of ICT equipment for elementary schools in the form of chromebooks, it is hoped that digitalization-based learning can be realized. Sungai Kakap 18 Public Elementary School is a driving school that has received chromebook assistance from the Ministry of Education and Culture. The purpose of this study was to analyze the implementation of learning by utilizing chromebooks in class IV SD Negeri 18 Sungai Kakap. This type of research used qualitative research. The data source for this research is a person, namely the homeroom teacher. The data collection technique used is technical triangulation, with data collection tools used interviews and observation sheets. Qualitative data analysis is inductive in nature including data reduction, data presentation, conclusion/verification). Based on the results of the studies that have been carried out, it can be interpreted that 1) the teacher has utilized most of the existing applications in the cromebook cromebook in science learning in grade 4; 2) The interaction between students and teachers has a high intensity when compared to the learning process which is carried out without using chromebook media; 3) The use of digital cromebook media in social studies learning shows that it is quite adequate in most of the applications commonly used in learning activities; 4) Student responses to the features of the Chromebook used during science teaching and learning activities in class; for them it is very pleasant, the more excited; learning using chromebooks makes it easier for them to understand learning and easily find learning material or resources; and 5) Students don't feel the need to carry a lot of books every day to attend lessons at school.